(untitled) (Papeles, 2009)
Abstract. This article aims at taking a close look at the street monuments in Bogota city related to the Colombian Independence and analyze not only the meaning those monuments have in relation with the Independence and the construction of the historic memories but also the historic context in which they were raised and the artists who created them.